Prospective randomized trial comparing two doses of rabbit anti‐thymocyte globulin in patients with severe aplastic anaemia. (17th June 2019) - Narita, Atsushi; Zhu, Xiaofan; Muramatsu, Hideki; Chen, Xiaojuan; Guo, Ye; Yang, Wenyu; Zhang, Jingliao; Liu, Fang; Jang, Jun H.; Kook, Hoon; Kim, Hawk; Usuki, Kensuke; et al.
Summary: The treatment of choice for patients with severe aplastic anaemia (SAA) includes immunosuppressive therapy (IST) with anti‐thymocyte globulin (ATG) and ciclosporin A. However, the optimal dose for rabbit ATG has yet to be established. We herein report the first prospective, randomized, multicentre study comparing two doses of rabbit ATG in patients with SAA. Patients with SAA who required initial IST in Japan ( n = 89), China ( n = 85) and Korea ( n = 48) were enrolled between May 2012 and October 2017. A 1:1 block randomization was employed for two doses of rabbit ATG. In total, 222 patients were randomized, with 112 patients receiving 2·5 mg/kg and 110 receiving 3·5 mg/kg of rabbit ATG for 5 days. The primary endpoint was the haematological response at day 180. After 6 months, no significant difference in response rates was observed between the 2·5 and 3·5 mg/kg groups (49% vs. 48%, P = 0·894). Overall survival at 3 years was similar between the two groups [85% (95% confidence interval [CI], 76%−91%) vs. 91% (95% CI, 82%−96%); P = 0·107]. The current study revealed no significant differences in the efficacy and safety between the 2·5 and 3·5 mg/kg doses of rabbit ATG in patients with SAA. Trial registration: UMIN000011134.